2001
DOI: 10.1152/jappl.2001.90.6.2445
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body heat content and finger temperature during cold exposure

Abstract: The purpose of the present experiment was to examine the relationship between rate of body heat storage (S), change in body heat content (DeltaH(b)), extremity temperatures, and finger dexterity. S, DeltaH(b), finger skin temperature (T(fing)), toe skin temperature, finger dexterity, and rectal temperature were measured during active torso heating while the subjects sat in a chair and were exposed to -25 degrees C air. S and DeltaH(b) were measured using partitional calorimetry, rather than thermometry, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 34 publications
4
31
2
Order By: Relevance
“…The effect of the bath temperature was confined to the two smallest track widths for the movement time and to the smallest track width for the number of errors. These results are similar to those of the gross finger dexterity and fine finger dexterity seen in other studies, such as that by Brajkovic et al (2001), where there were no differences in a C-7 rifle assembly and disassembly task with bare hands and gloved hands. The effects of the reduced hand/skin temperature are clearly in the reduction in fine motor control.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The effect of the bath temperature was confined to the two smallest track widths for the movement time and to the smallest track width for the number of errors. These results are similar to those of the gross finger dexterity and fine finger dexterity seen in other studies, such as that by Brajkovic et al (2001), where there were no differences in a C-7 rifle assembly and disassembly task with bare hands and gloved hands. The effects of the reduced hand/skin temperature are clearly in the reduction in fine motor control.…”
Section: Discussionsupporting
confidence: 91%
“…However, it should also be noted that wearing gloves will increase the muscular load requirement for a given task and will also hamper 15 handling small objects as tactile sensitivity is reduced (Buhman et al, 2000). The effects of using gloves or other suitable protection as a safety measure needs to be determined, because although gloves may protect hands against damage, they may well have an effect more detrimental to tracking performance than the lower temperature has, as finger dexterity has been found to be seriously impaired with gloves (Bishu et al, 1987;Brajkovic et al, 2001;Havenith and Vrijkotte, 1993). The hand-skin temperature will be slightly higher than the bath temperature due to the relatively short immersion time; the results need to be considered in terms of this limitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These parameters have been T ha and T fi , body heat content (H b ) and changes in body heat content (∆H b ) [7][8][9][10] . Gaydos and Dusek 10) looked at the effect of local versus total body cooling and concluded that T fi seemed to be the primary determinant of impaired manual performance.…”
Section: Introductionmentioning
confidence: 99%